Treating HR+/HER2− breast cancer in premenopausal Asian women: Asian Breast Cancer Cooperative Group 2019 Consensus and position on ovarian suppression - Yeo, Winnie; Ueno, Takayuki; Lin, Ching-Hung; Liu, Qiang; Lee, Kyung-Hun; Leung, Roland; Naito, Yoichi; Park, Yeon Hee; Im, Seock-Ah; Li, Huiping; Yap, Yoon Sim; Lu, Yen-Shen (Breast cancer research and treatment, 2019)
Purpose Breast cancer in young Asian women has distinctive clinicopathological characteristics; hence, we question the universal generalizability of treatment recommendations based on data from predominantly non-Asian postmenopausal women. Methods The Asian Breast Cancer Cooperative Group (ABCCG) reviewed current ESO-ESMO and St. Gallen recommendations for treating hormone receptor positive/human epidermal growth factor receptor 2 negative (HR+/HER2−) breast cancer in premenopausal women. Points disputed by ≥ 3/12 members were discussed, and statements on contentious issues formulated for anonymous voting; consensus required a ≥ 75% majority. Results The ABCCG contends that: (1) Trials in premenopausal women are not only necessary, but also worthwhile if performed separately from others that also enroll postmenopausal participants. (2) Not all premenopausal women with HR+ early breast cancer need adjuvant ovarian function suppression (OFS). (3) Certain clinical factors might influence decision-making about prescribing OFS. (4) For early HR+/HER2− breast cancer in premenopausal patients with OFS, tamoxifen is preferred for intermediate-risk cases; for high risk, near-consensus supported aromatase inhibitor, despite no clear overall survival benefit versus tamoxifen. (5) Oncotype DX Breast Recurrence Score ® has different treatment implications in patients aged ≤ 50 versus > 50 years. (6) High-risk patients (if premenopausal after chemotherapy) should receive adjuvant chemotherapy and OFS plus aromatase inhibitor. (7) For patients with advanced disease receiving OFS on a backbone of tamoxifen, gonadotrophin-releasing hormone agonists may be given 12-weekly. (8) For premenopausal women who decline OFS or oophorectomy, tamoxifen alone is still an option but is considered less effective; other monotherapies are also less effective than OFS plus such treatments. Conclusion Premenopausal Asian women with breast cancer have unique disease characteristics and may benefit from treatment that differs somewhat from international guidelines. Given the great diversity of patients and clinical settings worldwide, the ABCCG advocates evidence-based yet flexible and individualized use of all potential options to improve breast cancer outcomes.